2008
DOI: 10.1016/j.sbi.2008.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Protein dynamics from time resolved UV Raman spectroscopy

Abstract: SummaryRaman spectroscopy can provide unique information on the evolution of structure in proteins over a wide range of time-scales; the picosecond to millisecond range can be accessed with pump-probe techniques. Specific parts of the molecule are interrogated by tuning the probe laser to a resonant electronic transition, including the UV transitions of aromatic residues and of the peptide bond. Advances in laser technology have enabled the characterization of transient species at an unprecedented level of str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 40 publications
(48 reference statements)
2
62
0
Order By: Relevance
“…This view has been most prominently propagated in the works of the Frauenfelder, Freire, Nussinov, and Wolynes groups (6,(36)(37)(38)(39). The experimental hints in support of this new paradigm, were provided over the years by a variety of different techniques (40,41), in particular by NMR (19) and other spectroscopic methods (42). Recently, single-molecule studies allowed us to glimpse into the distribution itself (ion channel opening, kinesins walking on tubulin).…”
Section: Discussionmentioning
confidence: 99%
“…This view has been most prominently propagated in the works of the Frauenfelder, Freire, Nussinov, and Wolynes groups (6,(36)(37)(38)(39). The experimental hints in support of this new paradigm, were provided over the years by a variety of different techniques (40,41), in particular by NMR (19) and other spectroscopic methods (42). Recently, single-molecule studies allowed us to glimpse into the distribution itself (ion channel opening, kinesins walking on tubulin).…”
Section: Discussionmentioning
confidence: 99%
“…The instrument response is rapid. For example, structural changes of proteins occurring within a picosecond-to-millisecond range have been successfully monitored by using UV Raman spectroscopy (75). Other important protein conformational changes, such as alpha-helix peptide folding and unfolding, can be monitored by using UV resonance Raman spectroscopy on a nanosecond time scale (68).…”
Section: Discussionmentioning
confidence: 99%
“…To obtain more information about the structure and function of quinones, Raman spectroscopy is an incisive technique for studying aqueous biological samples giving fingerprint information on the chemical bond vibrations of target molecules [9,10]. Previous Raman investigations of benzoquinone (BQ), BQ anion radicals, and benzoquinols have shown that the C-O associated vibrations of these three species are distinguishable [11][12][13].…”
Section: Introductionmentioning
confidence: 99%